2013
DOI: 10.1021/ja408652h
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Value of Injection Current and Effective Electrical Contact Area for EGaIn-Based Molecular Tunneling Junctions

Abstract: Analysis of rates of tunneling across self-assembled monolayers (SAMs) of n-alkanethiolates SC n (with n = number of carbon atoms) incorporated in junctions having structure Ag TS -SAM//Ga 2 O 3 /EGaIn leads to a value for the injection tunnel current density J 0 (i.e., the current flowing through an ideal junction with n = 0) of 10 3.6±0.3 A·cm −2 (V = +0.5 V). This estimation of J 0 does not involve an extrapolation in length, because it was possible to measure current densities across SAMs over the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
553
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 242 publications
(608 citation statements)
references
References 55 publications
52
553
3
Order By: Relevance
“…Since the structural elements in this region differ from those in the region where there are data (the region of Ph n ) extrapolation may be inappropriate for S(Ph) n and C≡C(Ph) n , although the correction of this extrapolation is well-validated for nalkanethiolates on gold and silver. 2,12 …”
Section: Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the structural elements in this region differ from those in the region where there are data (the region of Ph n ) extrapolation may be inappropriate for S(Ph) n and C≡C(Ph) n , although the correction of this extrapolation is well-validated for nalkanethiolates on gold and silver. 2,12 …”
Section: Notesmentioning
confidence: 99%
“…1 Among the exceptions are the observation of a small "odd-even effect" in charge transport across n-alkanethiolates on gold, [2][3][4] the observation of a substantial reduction in current density when fluorine is present at the SAM//Ga 2 O 3 interface, 5 and the observation of rectification of current when T is a redox active group such as ferrocenyl [6][7][8] or bipyridyl. 9 Having studied the influence of the structure of saturated n-alkyl groups on charge tunneling extensively, [10][11][12][13][14][15] we turned our attention to understanding the relationship between the structure of polyaromatics (molecules that result in a reduction in the height of the tunneling barrier relative to that characterizing aliphatics 16 ) and the rates of charge transport. We measured rates of charge transport across SAMs of oligophenylthiols (M/SPh n ), -methanethiols (M/SCH 2 Ph n ), and -acetylenes (M/C≡CPh n ), where n = 1-3 and M = gold and silver metal electrodes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39, 40 Junctions comprising Ga 2 O 3 /EGaIn and HOPG result in an ohmic metal/semiconductor interface; that is, the current density, J, varies linearly with the applied voltage. 1 By using a freshly formed HOPG surfacegenerated by mechanical cleavage of the top layers of a piece of graphite glued to a metal shimwe could create a clean, flat, electrically conducting surface (root mean square (rms) roughness of 0.3−0.5 nm, according to SPI technical specifications). By using graphite electrodes, we were able to attribute the majority of the variations observed as a result of changes in the environment to the Ga 2 O 3 film, rather than to some other part of the junction.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Simeone et al 1 have compared a liquid drop of Hg and a conical tip Ga 2 O 3 /EGaIn electrode in measurements of a Fe/ FeO X substrate, where the FeO X was the most-resistive component of the junction. They created electrodes with equivalent nominal contact areas, and found that the current density of the conical tip electrode was ∼10 −3 × lower than the value measured from the Hg-drop electrode.…”
Section: ■ Introductionmentioning
confidence: 99%